Reproductive Performance of Bali Cattle in Tinanggea Subdistrict, South Konawe District - Khairiyah, Ummul; Aku, Achmad Selamet; Saili, Takdir; Asminaya, Nur Santy (Pascasarjana Universitas Halu Oleo, 2024)
This research aims to evaluate the Reproductive Performance of Bali Cattle in Tinanggea District, South Konawe Regency. The method used in this research is the quantitative descriptive method which is defined as a method that aims to create a picture or description of a situation using numbers, starting from data collection, interpretation of the data as well as the appearance and results. The research variables observed were the mating system, service per conception (S/C), and calving interval (CI). Based on the research results, the reproductive performance of Bali cattle in Tinanggea District where the mating system used was 96% natural mating, while the number of matings carried out until the cattle become pregnant or the average Service per conception is 1.72 times and the Calving interval (CI) is 12.45 months. It is necessary to carry out further research regarding the reproductive performance of Bali cattle in Tinanggea District and provide education regarding artificial insemination (AI) and livestock breeding systems patterns so that breeders have a better understanding.